Small and medium enterprises’ business sustainability based on the Industry 4.0 internet of things adoption: a Malaysian Bumiputera case study - Abd Shukor, Rijal; Mooi, Wah Kian; Ahmad , Mohammad Nazir (Serbian Journal of Management, 2022)
Companies of all sizes, including Small and Medium Enterprises, have been left with few choicesfor preparing for and implementing changes. This research gathered information to provide thetheoretical framework on the determinants that Malaysian Bumiputera SMEs are relying on for theirdecision to adopt or not to adopt IoT in their business operations. Bumiputera refers to the indigenouspeople of Malaysia. The study utilised a cross-disciplinary study design. The data was obtained fromcompany proprietors in Malaysia that operate in the category of Bumiputera SMEs and wasstatistically analysed using IBM's SPSS and AMOS software. According to the initial findings, it canbe seen that respondents are very excited about the benefits of IoT, but lack the imagination topioneer the arrangement. Furthermore, even though respondents are unconcerned about IoT, it givesthe appearance of being unsure, leading them to think further on whether to trust it or not. It was alsoshown that top organizations have an increasingly good intuition of IoT, but also a progressivelynegative intuition of it. It is recommended that SMEs holistically, especially Bumiputera SMEs,acquire more knowledge and be prepared to expand the grasp of productive factors of IoT inMalaysia
Keywords: Small Medium Enterprises (SMEs); Bumiputera SMEs; Business Sustainability; Industry 4.0; The Internet of Things (IoT); TOE Framework